Determinants of Poverty among Households in Bhutan - Chimmi,; Unhapipat, Suntaree (International Journal of Psychosocial Rehabilitation, 2020)
This study investigates the demographic factors that affect the poverty status of households in Bhutan. A sample of 11,654 households from Bhutan Living Standard Survey conducted by the National Statistical Bureau in 2017 was used for the analysis. A logistic regression was performed with the poverty status (poor and non-poor) as an outcome variable and a set of demographic factors as the predictor variables. Further, the predictor variable were tested using Chi-square test at 0.05 level of significance. The poverty status of each household was determined by comparing Person’s consumption expenditure with a standard poverty line of Nu 2,195.95 per person per month. The demographic factors showed significant influence on poverty status of the household, especially age and gender of household head, household size, qualification and employment status of household head, marital status and residence of household.